GDP Effect on B2C E-commerce Turnover and Number of Express Shipments in Selected European Post-Communist Countries - Michaela Novotná; Dalibor Gottwald; Libor Švadlenka (Communications - Scientific letters of the University of Zilina, 2021)
The impact of the e-economy has been observable in almost all the sectors of the national economies of the states in the last few years. The growing influence of this phenomenon is due to development of the Internet, which has already become a viable part of almost all the business activities including buying and selling. Therefore, it can be assumed that the area of e-commerce will have an increasing impact, not only on national economic development, but on the express mail market, as well. The content of the article is designed to provide a comprehensive view of the interdependence between the level of economic maturity (the GDP gross Domestic Product) per capita in the PPS (Purchase Power Standard) indicator), development of the e-commerce (indicator B2C (Business to Customer) e-commerce turnover) and the number of express deliveries. Identifying the influence between the aforementioned indicators, it will be possible to take certain measures to support the development of the e-commerce market.